138k views
3 votes
2(2-x) =4(-2+x)
What’s the answer?
(With work please)

User Simon Degn
by
5.4k points

1 Answer

6 votes

Answer: x=2

Step-by-step explanation: Step 1: Simplify both sides of the equation.

2(2−x)=4(−2+x)

(2)(2)+(2)(−x)=(4)(−2)+(4)(x)(Distribute)

4+−2x=−8+4x

−2x+4=4x−8

Step 2: Subtract 4x from both sides.

−2x+4−4x=4x−8−4x

−6x+4=−8

Step 3: Subtract 4 from both sides.

−6x+4−4=−8−4

−6x=−12

Step 4: Divide both sides by -6.

−6x

−6

=

−12

−6

x=2

User Bpgeck
by
4.4k points